Study on the addition of SiO2 nanowires to BaTiO3: Structure, morphology, electrical and dielectric properties. (September 2021) - Slimani, Y.; Selmi, A.; Hannachi, E.; Almessiere, M.A.; AlFalah, Gaeet; AlOusi, Latifa F.; Yasin, Ghulam; Iqbal, Munawar
Abstract: The effects of adding silicon dioxide (SiO2 ) nanowires on the properties of barium titanate (BaTiO3 ) were investigated. The structure, morphology and optical properties were examined using X-ray powder diffraction (XRD), Fourier transform-infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and ultraviolet–visible diffuse reflectance spectrophotometry (DR). All of the prepared samples crystallized with a cubic BaTiO3 structure. When the SiO2 content was <2.0 wt%, no secondary phase was observed and the (BaTiO3 )1–x /(SiO2 )x samples exhibited a microstructure with small grains. However, Ba2 TiSi2 O8 was detected upon further increasing the SiO2 content. When compared to the pure BaTiO3 sample, a slight increase in the E g value was observed for the (BaTiO3 )1–x /(SiO2 )x composites. The dielectric and electrical measurements were used to analyze the dielectric constant ( ε′ ), dissipation factor (tan(δ)), conductivity ( σ ac ) and impedance ( Z ). The results demonstrate that the addition of SiO2 nanowires affects the properties of BaTiO3 . The study highlights the importance of SiO2 nanowires in BaTiO3 for use in microwave device applications. Highlights: BTO + x SiO2 nanowire (x = 0.0–2.0 wt%) ceramics were prepared. All the prepared samples crystallized with a cubic BaTiO3 structure. The grain size decreased upon increasing the SiO2 nanowires content. The band gap energy ( E g )slightly increased with the addition of SiO2 nanowires. The samples prepared with x = 0.5 and 1.0% exhibited low dielectric loss and good stability over the frequency range studied.